Project Éden: platform for introductory programming concepts - Oliveira, Yure Pablo do Nascimento; Toledo, Claudio Fabiano Motta; Pereira, Leonardo Tórtoro (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
The area of programming is perceived as complex and requires challenging skills, and programming courses have some of the highest dropout rates. Educational games are good solutions to these problems as they promote student engagement and an immersive learning experience. In this context, the present paper discuss the development and the validation of a more complete and more playful version of the Project Éden game, which aims to improve the learning process of coding. The player needs to instantiate variables and modify their values, and also must interpret, choose, and adjust in code form to advance through the stages and reach the final challenge. The game was developed with a methodology based on the evolutionary prototype concept. A set of users evaluated the game, and the results reported a satisfactory user experience. The game was considered fun with valuable tips for solving problems with content approached playfully and understandably by undergraduate, graduate students, and professors.